Hosszú távú összehasonlító cönológia vizsgálat a Tihanyi-félszigeten, Balaton-felvidéki Nemzeti Park, Magyarország - Szabó, Gábor; Magyar, Veronika; Szentes, Szilárd; Penksza, Károly (Gyepgazdálkodási Közlemények, 2022)
Phytosociological samples were collected in two territories of the Balaton Uplands National Park (Hungary) dominated by grassland habitats. Samples in the Tihany Peninsula had been taken in a pasture of Hungarian Grey Cattle. We evaluated the changes of species composition and ground cover, the measure of possible regeneration or degradation, and the changes of these factors from the viewpoint of feeding value.